Whole-Exome Sequencing Reveals a Missense Variant c.1612C>T (p.Arg538Cys) in the BTD Gene Leading to Neuromyelitis Optica Spectrum Disorder in Saudi Families - Naseer, Muhammad Imran; Pushparaj, Peter Natesan; Abdulkareem, Angham Abdulrahman; Muthaffar, Osama Y. (Frontiers in Pediatrics, 2022)
Biotinidase deficiency is an autosomal recessive, multiple carboxylase deficiency usually associated with seizures, eczema, hypotonia, visual disturbances, hearing loss, and developmental delays. Only a handful of cases of biotinidase deficiency that had clinical features of neuromyelitis optica spectrum disorder have been reported in the literature. The case report study is about the clinical and genetic features of two pediatric patients from different families with biotinidase deficiency whose brain and spine MRI scans were suggestive of neuromyelitis optica. Neither child improved with immunotherapy. They come from a first-degree blood-related family. In both cases, a deficiency of the enzyme biotinidase was detected. The missense variant NM_001370658.1 (BTD):c.1612C>T (p.Arg538Cys) NM_000060.4 in exon 4 was identified by whole-exome sequencing. The identified sequence variation was validated using Sanger sequencing analysis. The intake of biotin resulted in clinical improvement. After a follow-up period of 12 months, the patient was gradually weaned from tracheostomy. His vision had improved significantly. He was able to walk and run independently. In conclusion, biotinidase deficiency is a rare and treatable cause of neuromyelitis optica. Early diagnosis can prevent poor clinical outcomes. Biotinidase enzyme levels should be considered as part of the examination algorithm for neuromyelitis optica spectrum disorder.